Les oeuvres de l'Association de Bienfaisance Musulmane de la ville de Saïda, Libanon = The works of the Benevolent Islamic Makassed Society of Sidon, Lebanon. (S.l. : s.n., 1950)
Bibliotheek Camille Huysmans
Frans
Engels
Arabisch
Brochure
Keywords: onderwijs; islam; Libanon